Comment on "The embodiment of Confucian thought in Chinese classical dance performance" - Li, Qianwen (2024)
Commented article: LONG, X. The embodiment of Confucian thought in Chinese classical dance performance. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 5, e02400241, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15886.